Entrepreneurship and job satisfaction: The role of age - Michael Fritsch; Alina Sorgner; Michael Wyrwich (Friedrich Schiller University Jena, 2018)
This paper investigates the relationship between job satisfaction and age for self-employed persons as compared to paid employees. While, on average, there are higher levels of job satisfaction in self-employment as compared to paid employment, we find that an individual's age is an important moderator in this relationship. Specifically, the probability of the self-employed to experience high levels of job satisfaction is quite similar across all age cohorts, but the job satisfaction of paid employees varies significantly with age. The degree to which self-employed people are more satisfied with their work than paid employees, therefore, is affected by the age of the individuals involved. We find that only those paid employees at the final stage of their working life have the same probability of experiencing a high level of job satisfaction as a self-employed person with comparable individual characteristics.
Keywords: L26; I31; J10; D91; 330; entrepreneurship; well-being; job satisfaction; age